A generalization of a theorem by Cheo and Yien concerning digital sums - Curtis N. Cooper; Robert E. Kennedy (International Journal of Mathematics and Mathematical Sciences)
For a non-negative integer n, let s(n) denote the digital sum of n. Cheo and Yien proved that for a positive integer x, the sum of the terms of the sequence{s(n):n=0,1,2,…,(x−1)}is (4.5)xlogx+0(x). In this paper we let k be a positive integer and determine that the sum of the sequence{s(kn):n=0,1,2,…,(x−1)}is also (4.5)xlogx+0(x). The constant implicit in the big-oh notation is dependent on k.